Minat Generasi Z di Kabupaten Aceh Barat untuk Berkunjung ke Destinasi Wisata Sejarah Makam Teuku Umar - Qudus, Sultan Ruhil; Yusnaidi, Yusnaidi (Universitas Teuku Umar, 2024)
As the heirs of civilization, Generation Z exhibits interest in visiting historical tourist destinations, demonstrating that they still harbor a sense of nationalism that never forgets the history of heroes. As Bung Karno once said,